Kere Alang Promotion Strategy for Poto Village in Supporting Tourism Development in Sumbawa Regency - Qamilla, Zillati; Supriadi, Erri; Mahsyar, Lalu (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
This qualitative research study aimed to design an effective promotion strategy for Kere Alang Poto Village to increase its visibility among the wider community. The study used a combination of research methods, including observation, in-depth interviews, and documentation to collect data. The findings showed that organizing events and utilizing online marketing were effective strategies in promoting Kere Alang woven fabrics, supporting tourism development in Sumbawa Regency. The study's main contribution is providing insights into effective promotion strategies that can help support the growth of the local economy and tourism industry in Sumbawa Regency. Additionally, the study's use of SWOT analysis to analyze the research data can be useful for researchers and practitioners in developing promotional strategies for similar contexts